Prosecutors and democracy : a cross-national study / edited by Maximo Langer, David Alan Sklansky. - Langer, Máximo; Sklansky, David A., 1959- (ASCL studies in comparative law, 2017)
Focusing on the relationship between prosecutors and democracy, this volume throws light on key questions about prosecutors and the role they should play in liberal self-government. Internationally distinguished scholars discuss how prosecutors can strengthen democracy, how they sometimes undermine it, and why it has proven so challenging to hold prosecutors accountable while insulating them from politics. The contributors explore the different ways legal systems have addressed that challenge in the United States, the United Kingdom, and continental Europe. Contrasting those strategies allows an assessment of their relative strengths - and a richer understanding of the contested connections between law and democratic politics. Chapters are in explicit conversation with each other, facilitating comparison and deepening the analysis. This is an important new resource for legal scholars and reformers, political philosophers, and social scientists.